Compression of morbidity: postponing human aging - Fries, James (Henry Stewart Talks, 2016)
Insights into human aging, The compression of morbidity: central thesis, Reduction in health risks postpones aging, Delay aging by lifelong exercise, Exercise and morbidity, Actions that postpone aging, Multiple controlled longitudinal studies